Captive Rearing Success and Critical Thermal Maxima of Bombus griseocollis (Hymenoptera: Apidae): A Candidate for Commercialization?. Issue 6 (18th November 2022) - Christman, Morgan E; Spears, Lori R; Koch, Jonathan B U; Lindsay, Thuy-Tien T; Strange, James P; Barnes, Cody L; Ramirez, Ricardo A
Abstract: Commercialized bumble bees ( Bombus ) are primary pollinators of several crops within open field and greenhouse settings. However, the common eastern bumble bee ( Bombus impatiens Cresson, 1863) is the only species widely available for purchase in North America. As an eastern species, concerns have been expressed over their transportation outside of their native range. Therefore, there is a need to identify regionally appropriate candidates for commercial crop pollination services, especially in the western U.S.A. In this study, we evaluated the commercialization potential of brown-belted bumble bees ( Bombus griseocollis De Geer, 1773), a broadly distributed species throughout the U.S.A., by assessing nest initiation and establishment rates of colonies produced from wild-caught gynes, creating a timeline of colony development, and identifying lab-reared workers' critical thermal maxima (CTMax ) and lethal temperature (ecological death). From 2019 to 2021, 70.6% of the wild-caught B. griseocollis gynes produced brood in a laboratory setting. Of these successfully initiated nests, 74.8% successfully established a nest (produced a worker), providing guidance for future rearing efforts. Additionally, lab-reared workers produced from wild-caught B. griseocollis gynes had an average CTMax of 43.5°C and an average lethal temperature of 46.4°C, suggesting B. griseocollis can withstand temperatures well above those commonly found in open field and greenhouse settings. Overall, B. griseocollis should continue to be evaluated for commercial purposes throughout the U.S.A.